LEGAL PROTECTION FOR CONSUMERS OF E-2B BANDA ACEH REFILL DRINKING WATER DEPOT IN TERMS OF INDONESIAN POSITIVE LAW AND ISLAMIC LAW - Muhammad Arief; Agustin Hanapi; Nilam Sari (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
Article 1 of Law No. 8 of 1999 which regulates